Contracts as rent seeking devices: evidence from German soccer - Eberhard Feess; Michael Gerfin; Gerd Muehlheusser (Institute for the Study of Labor (IZA), 2008)
Recent theoretical research has identified many ways how contracts can be used as rent seeking devices vis-à-vis third parties, but there is no empirical evidence on this issue so far. To test some basic qualitative properties of this literature, we develop a theoretical and empirical framework in the context of European professional soccer where (incumbent) clubs and players sign binding contracts which are, however, frequently renegotiated when other clubs (entrants) want to hire the player. Because they weaken entrants in renegotiations, long term contracts are useful rent seeking devices for the contracting parties. From a social point of view, however, they lead to allocative distortions in the form of deterring efficient transfers. Since incumbent clubs tend to benefit more from long term contracts in renegotiations than players, these must be compensated ex ante by a higher wage when agreeing to a long term contract. Using data from the German Bundesliga, our model predictions are broadly confirmed. In particular, our analysis supports the concerns expressed in the theoretical literature about detrimental effects of strategic contracting on allocative inefficiency.
urn:nbn:de:101:1-20081127630
Keywords: L14; 330; Strategic contracting; rent seeking; empirical contract theory; long-term contracts; breach of contract; sports economics; Arbeitsvertrag; Vertragstheorie; Rent Seeking; Fußballsport; Professioneller Sport; Sportler; Lohnverhandlungen; Deutschland